Engineering a bandgap-regulable intermediate-band material based on diamond. (May 2022) - Dong, Xiao; Qiao, Rong; Wang, Tianxing; An, Yipeng; Wang, Yongyong
Abstract: A diamond-based material C63-x Six V compound is engineered by using density functional theory calculations. In the C63-x Six V compound, (1 + x) C atoms in the 2 × 2 × 2 diamond supercell are replaced by x Si and one V atoms. In this way, a bandgap-regulable intermediate-band (IB) photovoltaic material would be gotten. The calculational results indicate that it can reduce the bandgap of the diamond without changing the character of its band structure to substitute Si atoms for several C atoms in the diamond. And the bandgap decreases along with the increase of Si content. When the atomic concentration of Si is lower than 6.25%, the implantation of Si has less effect on the width and electron filling of the IB for the C63-x Six V compound. With the increase of Si content, the IB in the bandgap shifts toward the VB and the sub-bandgap absorption of the C63-x Six V compound shifts to longer wavelength range. Results of partial density of states indicate that the IB formed by implanting V in the diamond is mainly composed of the d states of V, while the contribution of the Si is negligible. Graphical abstract: Image 1